Financial uncertainty and the cross-section of cryptocurrency returns - Colak, Gonul; Vedova, Joshua Della; Foley, Sean; Mai, Sinh Thoi (Journal of Banking & Finance, 2026)
Our study evaluates the return sensitivity of cryptocurrencies to various measures of uncertainty (uncertainty beta). We identify that crypto returns react primarily to financial uncertainty, which is the unforecastable component of multiple financial indicators. However, crypto returns are not sensitive to other forms of uncertainty such as macro, real, or policy uncertainty, as well as VIX, and inflation. The portfolio analysis yields a significant financial uncertainty premium of around 21% per month, which is driven by the outperformance (underperformance) of cryptocurrencies with a negative (positive) uncertainty beta. The portfolio returns are more potent in coins with speculative, rather than transactional, features such as proof-of-work, non-token, and mineable. Our findings suggest that large investors exhibit a willingness to pay higher premiums for cryptocurrencies with positive uncertainty betas, as these assets can be used as a hedging tool within a larger financial portfolio.